Implementation of Digital Accounting on the Effectiveness of Corporate Social Responsibility and Environmental, Social, and Governance Reporting - Suhardjo, Suhardjo; Wati, Yenny; Renaldo, Nicholas; Musa, Sulaiman; Cecilia, Cecilia (First Ciera Publisher, 2024)
This study delves into the role of digital accounting systems in enhancing the quality and effectiveness of Corporate Social Responsibility (CSR) and Environmental, Social, and Governance (ESG) reporting. Findings indicate that digital accounting substantially improves reporting accuracy, timeliness, and transparency, enabling organizations to meet stringent regulatory standards and foster trust among stakeholders. Tools such as blockchain, ERP systems, and AI-driven analytics have streamlined the collection and processing of sustainability data, making reports more actionable and aligned with global benchmarks like GRI and SASB. Nevertheless, challenges such as high costs, data security issues, and organizational resistance were identified as barriers to widespread adoption. Addressing these challenges can further unlock the potential of digital accounting systems in driving sustainable business practices and enhancing corporate accountability.